Front Matter Vol. 12 No. 2 2019 - Statistika, Media (Department of Statistics, Faculty of Science and Mathematics, Universitas Diponegoro, 2019)
Cover dan Daftar Isi Media Statistika Vol. 12 No. 2 Desember 2019